Structural Characteristics of Sheep and Goat Husbandry in Çorum Province - Hacer Tüfekci; Başak Özten (Research in Agricultural Sciences)
The aim of the study is to determine the structural characteristics of sheep and goat farm in Çorum province, the problems faced by breeders and to offer solutions to these problems. The material for the study consisted of data obtained through personal interviews in 140 sheep and goat farms in the districts of Çorum province. In the study, it was determined that the breeders were mostly between 41-50 years old, their education level was secondary school (55.7%), the number of family members was 3-4 and their experience in the profession was 21-30 years. In the study, it was determined that females were used for breeding for 4-5 years and males for 3 years. It was determined that animal records were generally not kept on the farm and the need for shepherds in the family was met from the family (64.3%). In conclusion in addition to the problems of marketing and insufficient pastures, breeders also lack knowledge about cultivation and health protection and the potential in the region is not adequately reflected in production. In order to overcome these problems, it is necessary to increase and continue the support for the development of sheep and goat husbandry, improve health protection and social rights and encourage young people in particular.